Application of the Problem Based Learning Model to Improve Learner's Active Learning - Hilmiah Roskawati (BULLET : Jurnal Multidisiplin Ilmu, 2022)
−This research was conducted to increase the activeness of students' learning on the material of production costs. The researcher applies the Problem Based Learning (PBL) model with 20 students as research subjects. This research data collection technique was carried out systematically by using an observation questionnaire. Based on learning observations in the first cycle, the level of student activity is 40%. In the second cycle, learning adjusted to the results of the reflection of the first cycle was able to increase the active learning of students up to 60%. In the third cycle, the impact was able to increase the learning activity of students, which reached 95% of the number of students who were declared active in learning. From the findings and observations of the first cycle to the third cycle, it can be seen that there is a dominant increase and has reached the indicators of success set by the researcher. The researcher draws the conclusion that by applying the PBL learning model, it can increase the active learning of students. With these results, it is hoped that it can become a reference for other researchers to increase the learning activity of students.